2023
DOI: 10.1038/s41598-023-37819-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between statin therapy and mortality in patients on dialysis after atherosclerotic cardiovascular diseases

Abstract: Statin therapy is essential for secondary prevention in patients with atherosclerotic cardiovascular disease (ASCVD). However, the effects of statin therapy in patients receiving chronic dialysis remain uncertain. We aimed to evaluate the effect of statin therapy on long-term mortality in patients on dialysis after a first-time ASCVD. Patients receiving maintenance dialysis aged ≥ 18 years with a first-time ASCVD event between 2013 and 2018 were included in the Korean National Health Insurance Service database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…However, this recommendation was limited to the use of statins for primary prevention. Although the KDIGO guidelines do not provide recommendations for secondary prevention, recent research has suggested that using statins for secondary prevention after cardiovascular events may yield favorable outcomes [36][37][38]. Although we did not include data on the history of statin initiation, considering the limited efficacy of statins for primary prevention and the potentially favorable results for secondary prevention, we believe that many patients in our study may have used statins for secondary prevention.…”
Section: Discussionmentioning
confidence: 96%
“…However, this recommendation was limited to the use of statins for primary prevention. Although the KDIGO guidelines do not provide recommendations for secondary prevention, recent research has suggested that using statins for secondary prevention after cardiovascular events may yield favorable outcomes [36][37][38]. Although we did not include data on the history of statin initiation, considering the limited efficacy of statins for primary prevention and the potentially favorable results for secondary prevention, we believe that many patients in our study may have used statins for secondary prevention.…”
Section: Discussionmentioning
confidence: 96%